Teaching Competencies and Professional Commitment: Relationship to Job Satisfaction of Senior High School Teachers - Velasco, Marjorie S.; Baer, Jefferson S. (BOHR International Journal of Advances in Management Research, 2022)
This study determined the teaching competencies, professional commitment, and job satisfaction of 62 Senior High School Teachers from the Divisions of San Jose City, Nueva Ecija, Philippines. The findings showed that the mean age of the respondents was 35 years, females, Bachelor of Secondary Education graduates, had 0–4 years in teaching, were Licensure Examination for Teachers (LET) passers, and Teacher II in position. The teaching competency of the respondents was rated as strongly agree. Moreover, the professional commitment was rated as moderately agree. Job satisfaction was generally described as agree. The teaching competencies of the respondents were significantly correlated with job satisfaction. Furthermore, professional commitment has a negative relationship with the job satisfaction of the respondents.